A Man With Intractable Convulsion. Issue 4 (July 2015) - Xia, Yun; Cutrona, Anthony; Barreiro, Timothy J.
Abstract : Abstract: Tetanus is a rare disease in the United States. Fewer than 40 cases are reported annually because of the high incidence of vaccination. Recognition of the clinical presentations is important because laboratory recovery of pathogen is only 30%, and toxin detection is rare because of consumption at motor neurons. We report a case of tetanus in an elderly man who had a reaction to tetanus vaccination as a child and was nonvaccinated through adult life. Abstract : Supplemental digital content is available in the text.